Language Shift on Moi Community: An Initial Notes - Anggy Denok Sukmawati (TALENTA Publisher, 2023)
Moi is a Papuan Language spoken by Moi Community in Kabupaten Sorong, West Papua. We conduct a sociolinguistic research on this language to see the language attitude of Moi Community on their language. This is only an initial research and we need to dig deeper on the result. The results show Moi Community have a tendency to choose Bahasa Indonesia than their language. This attitude happened for several generations. Furthermore, their attitude towards their language leads to major shift on Moi Language. This paper will show the recent condition of Moi Language regarding this shift and efforts from local government to “save” Moi Language.